Schizophrenia: its psychological effects on family caregivers - Riley-McHugh, Delvalin; Hepburn Brown, Cerese; Lindo, Jascinth (International Journal of Advanced Nursing Studies, 2016)
Purpose: Caregivers of patients diagnosed with schizophrenia experience moderate to severe caregiver burden and are at risk for developing mental disorders. This study explores the psychological effects and coping strategies of family caregivers of relatives diagnosed with schizophrenia in the developing world.Methods: This qualitative study used the register of a community mental health clinic at a Jamaican hospital to purposively select and recruit five primary family caregivers of clients diagnosed with schizophrenia (based on the DSM IV). Consenting participants were interviewed using a semi-structured interview guide. Data were analyzed using thematic content analysis.Results: Four of the five caregivers studied were females. Participants were either parents (4) or siblings (1) of the client diagnosed with schizophrenia and aged 42 -57years. Participants experienced feelings of anger, sadness, loss of libido, loss of appetite and depression. They expressed feelings of fear, guilt, stigma and stress related to financial responsibilities in caring for their relatives. Coping mechanisms included social support from family members and their strong faith in God.Conclusion: Participants reported experiencing major psychological distress and ineffective coping. Community based management of individuals with schizophrenia should include strategies to support family caregivers.